PENGEMBANGAN AGROINDUSTRI SANGKO’ DI KECAMATAN SAPEKAN KABUPATEN SUMENEP - Alifia F.D; Syarif Imam Hidayat; Mubarokah Mubarokah (University of Jember, 2012)
The purpose of this research is to analyze the development of sangko’ production in sapeken sub district, to analyze the contribution of sanko’ agroinstry towards household revenue/income in Sapeken sub district and to analyze the future of sangko’ agroindustry development. To accomplish the first purpose, the analysis used is the trend one, second puspose using both income/revenue and contribution analusis moreover the third purpose using descriptive analysis. The development of sangko’ production volume per 4 months from Juni 2088 to Auggust 2012 tends to be increasing sangko’ production contribution towards household income shows a positive manner and the development of sangko’ production in Sapeken sub district is prosperous, it can be seen both from internal and eksternal factors in supporting sangko’ agroindustry development. Keywords : agroindustry, development based on local resources, sangko’